2011
DOI: 10.1158/1055-9965.epi-10-1280
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Depression and Subsequent Cancer Risk in Taiwan

Abstract: Background: Patients with depression are suggestive of having a tendency toward a marginally significant association with the subsequent cancer risk. The aim of this study was to evaluate the possible relationship between depression and cancer risk in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 8 publications
0
52
2
Order By: Relevance
“…13 Briefly, the NHI program began in March 1995 and incorporated 13 insurance programs that provided health care to 99% of the Taiwanese population. The program contracted with 97% of the hospitals and clinics on the island, and it provides comprehensive medical services, including outpatient and inpatient care, dental care, physical therapy, preventive care, and prescriptions.…”
Section: For Editorial Comment See Page 417mentioning
confidence: 99%
“…13 Briefly, the NHI program began in March 1995 and incorporated 13 insurance programs that provided health care to 99% of the Taiwanese population. The program contracted with 97% of the hospitals and clinics on the island, and it provides comprehensive medical services, including outpatient and inpatient care, dental care, physical therapy, preventive care, and prescriptions.…”
Section: For Editorial Comment See Page 417mentioning
confidence: 99%
“…Finally, it needs to be considered that all three studies finding negative associations between depression and breast cancer incidence [33,39,43] and six studies finding positive associations [40-42, 44, 47, 48] included fewer than 220 individuals that developed breast cancer, while all studies finding positive associations had numbers of individuals developing breast cancer ranging from 229 to 2,892 cases of breast cancer [38,45,46,[49][50][51]. Thus, the small number of breast cancer cases could be another explanation for the negative associations between depression and breast cancer incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The Bureau of NHI randomly reviews the records of 1 in 100 ambulatory care visits and 1 in 20 in-patient claims to verify the accuracy of the diagnoses [50]. Several studies have demonstrated the accuracy and validity of the diagnoses in the NHIRD [51,52,53]. …”
Section: Methodsmentioning
confidence: 99%